Chapter The Role of Prefixation in Old Church Slavonic - Kamphuis, Jaap (Biblioteca di Studi Slavistici, 2017)
In this paper, I analyse the role of prefixation in the Old Church Slavonic (OCS) verbal aspect system. For my analysis, I first need to establish how the aspect of OCS verbs can be determined. To that end, I use a combination of methods: morphological categorization, grammatical profiling and semantic analysis. My analysis shows that, although prefixation in most cases equals perfectivization in OCS, it does not create aspect pairs like suffixation does. This is mainly because of the fact that many simplex verbs in OCS are anaspectual, even when prefixed formations exist.